Physiological Impacts, Regulations, and Ethical Implications of Doping in Sports: A Systematic Literature Review - Nimrot Manalu; Fahri Ridwan; Sopater Ndruru (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2026)
Objectives: This systematic literature review aims to analyze the physiological impacts of doping substances in sports, examine current regulatory frameworks, and evaluate ethical implications for competitive integrity. The study synthesizes existing research to provide a comprehensive understanding of doping's multifaceted effects on athletic performance and sports governance. Methods: A systematic literature review was conducted using electronic databases including PubMed, Scopus, Web of Science, and SportDiscus from January 2010 to December 2024. Search terms included